1934
DOI: 10.1002/ardp.19342725107
|View full text |Cite
|
Sign up to set email alerts
|

Über die Absorptionsspektren der Alkaloide der Kolombowurzel und einiger Derivate des Berberins. (5. Mitteilung über die Alkaloide der Kolombowurzel)

Abstract: 817sondern auch bei der durch Reste des Naphthalins. So ist z. B. /%Naphthylimethylamin 150mal giftiger als Methylamin.Auch der Rest des Thiophens, der ja haufig die physikalischen, chemischen und physiologischen Eigenschaften ahnlich wie der Benzolr rest beeinflu&, steigert die Giftigkeit gegenuber Paramacien. So wirkt z. B. ein Derivat des 3,4Dihydrocisochinolins (gemaR Formel I, Tabelle 6), das als Rest R die asThienylgruppe besitzt, llmal starker als die entsprechende Verbindung, in der diese Gruppe durch … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
6
0

Year Published

1952
1952
1967
1967

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…The present series of studies confirmed that the absorption maxima of (3) and (4) were at 288 mi: (em~4,000-4,500) and that of (2) at 268 mu (emaa: below 1,000) (Fig. 4).…”
Section: (4) Position Of Auxochrome Group and Its Effectsupporting
confidence: 92%
See 4 more Smart Citations
“…The present series of studies confirmed that the absorption maxima of (3) and (4) were at 288 mi: (em~4,000-4,500) and that of (2) at 268 mu (emaa: below 1,000) (Fig. 4).…”
Section: (4) Position Of Auxochrome Group and Its Effectsupporting
confidence: 92%
“…The absorption bands of isoquinoline and tetrahydroisoquinoline have many points of similarity in detail but there is a marked difference in their absorption intensity. The absorption bands of tetrahydroisoquinoline (I), tetrahydroprotoberberine (2), and tetrahydroprotopapaverine (3) have similar intensity values, and' the shape of absorption curves and the position of absorption maxima are also very close to each other. …”
mentioning
confidence: 72%
See 3 more Smart Citations